Electrical power grid network optimisation by evolutionary computing - Oliver, John M.; Kipouros, Timoleon; Savill, Mark A. (Elsevier, 2014)
A major factor in the consideration of an electrical power network of the scale of a national grid is the calculation of power flow and in particular, optimal power flow. This paper considers such a network, in which distributed generation is used, and examines how the network can be optimized, in terms of transmission line capacity, in order to obtain optimal or at least high-performing configurations, using multi-objective optimisation by evolutionary computing methods.
Keywords: Multi-objective; Optimisation; Evolutionary Computing; Electrical Power; Grid